SYSTEM OF ARTIFICIAL INTELLIGENCE HUMAN SKIN DISEASE DIAGNOSIS USING FORWARD CHAINING METHOD WEB - Alin Tri Sentika (International Journal of Artificial Intelligence and Robotic Technology, 2021)
Skin disease is a disease that is dangerous and easily suffered many circles, due to lack of knowledge of skin disease they thought that all diseases associated with normal skin as a disease, but their assumption is not necessarily true. Or perhaps they suffer from other illnesses that are more dangerous than skin disease in the suffering so with the artificial intelligence system can help the community in gaining the desired information about disease outside especially skin diseases. System that has the ability as an expert to give certainty. Therefore, based on the needs of the physicians and the general public in addressing the shortage of doctors, it can be in the wake of software engineering with forwarding chaining method for diagnosing skin diseases by using a web-based system